Hearing Loss and Kidney Dysfunction: Finding a Unifying Diagnosis - Praveena Iruku; Puja Karanth; Hannah Tiu; Charity Kankam; Khaldoon Shaheen (Case Reports in Medicine)
Microscopic polyangiitis (MPA) is a systemic vasculitis that affects small caliber vessels, with renal and lung compromise. Diagnosis can be challenging; timely diagnosis and treatment are important to prevent devastating complication, particularly renal failure. We present a case of a patient with microscopic polyangiitis presented with renal and pulmonary involvements with concomitant sensorineural hearing loss. We provide diagnostic, therapeutic, and prognostic keys to microscopic polyangiitis.